Sleep problem, suicide and self-harm in university students: A systematic review. (April 2019) - Russell, Kirsten; Allan, Stephanie; Beattie, Louise; Bohan, Jason; MacMahon, Kenneth; Rasmussen, Susan
Summary: Suicide and self-harm behaviours represent public health concerns, and university students are a particularly high risk group. Identifying modifiable risk factors for the development and maintenance of suicidal thoughts and behaviours is a research priority, as prevention is crucial. Research examining the relationship between poor sleep and self-harm/suicidality within university students is, for the first time, systematically evaluated, critically appraised, and synthesised. This literature consistently demonstrates that insomnia and nightmares are associated with elevated suicide risk of suicidal thoughts and behaviours within this subpopulation of young adults. However, as findings are predominantly derived from cross-sectional investigations, the directionality of this relationship is not yet clear. While research investigating the psychological processes driving these relationships is in its infancy, preliminary findings suggest that thwarted belongingness, socio-cognitive factors and emotional dysregulation could be partly responsible. Methodological limitations are highlighted and a research agenda suggesting the key directions for future research is proposed. Continued research in this area - employing longitudinal designs, and testing novel theoretically derived hypotheses - will be crucial to the development of suicide prevention and intervention efforts.